Религия как социальная технология консолидации социума - Грабовец, О.; Яковенко, Ю. (Социология: теория, методы, маркетинг, 2001)
The article presents a new concept version of religion as a social technology processed by time and which makes it possible for social subjects to solve social problems in various socio-cultural practices. With the help of the socio-synergetic approach app - lied to interpretation of social matter represented in religion, Christianity is regarded as a substantial-system formation acting in accordance with laws of self-movement. The authors interpret Christianity as a multi-level social construction capable of turning into specific adaptive forms, like social institution, social ‘body’ or social person. Taking into account the structural-active nature of religion, there is concluded that consolidating potential of Christianity greatly depends on its social self-reflexion and self-referention, on its ability to react effectively to modern challenge.